2022
DOI: 10.3389/fevo.2021.816918
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Bacterial Community Structure in Rhizosphere and Bulk Soils of Different Halophytes in the Yellow River Delta

Abstract: Soil microorganisms play the important role in driving biogeochemical cycles. However, it is still unclear on soil microbial community characteristics and microbial driving mechanism in rhizosphere and bulk soils of different halophyte species. In this study, we analyzed bacterial communities in the rhizosphere and bulk soils of three typical halophytes in the Yellow River Delta, i.e., Phragmites communis, Suaeda salsa, and Aeluropus sinensis, by high-throughput sequencing. The contents of total carbon, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
(38 reference statements)
2
24
0
Order By: Relevance
“…Plant root secretion of mucus, shed cells and tissues, and soluble products of ruptured cells all contribute to the TC and SOM of rhizosphere soil (Zhao et al, 2022). In addition, sugars and amino acids secreted by plant roots increase N availability in the soil (Zhao et al, 2022). In this study, the rhizosphere soil contained higher TN, SOM, and TC content compared to the bulk soil, which is evidence that the plant rhizosphere effect is at work.…”
Section: N-p Addition Ratio and Rhizosphere Effect On Soil Environmen...supporting
confidence: 55%
See 2 more Smart Citations
“…Plant root secretion of mucus, shed cells and tissues, and soluble products of ruptured cells all contribute to the TC and SOM of rhizosphere soil (Zhao et al, 2022). In addition, sugars and amino acids secreted by plant roots increase N availability in the soil (Zhao et al, 2022). In this study, the rhizosphere soil contained higher TN, SOM, and TC content compared to the bulk soil, which is evidence that the plant rhizosphere effect is at work.…”
Section: N-p Addition Ratio and Rhizosphere Effect On Soil Environmen...supporting
confidence: 55%
“…Plant root secretion of mucus, shed cells and tissues, and soluble products of ruptured cells all contribute to the TC and SOM of rhizosphere soil (Zhao et al, 2022). In addition, sugars and amino acids secreted by plant roots increase N availability in the soil (Zhao et al, 2022).…”
Section: N-p Addition Ratio and Rhizosphere Effect On Soil Environmen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 325 isolates, 315 amplified the BOX elements, forming bands from 228 to 1,736 bp, which identified 243 strains (Table 2), 78% of which were isolated at a single time, which indicates high diversity. This high diversity was also observed when plant parts or sampling areas were compared through the diversity indexes (Table 2), while dominance, equability, and high Margalef 's richness indexes confirmed that the strains were equally abundant, which usually indicates greater stability and resistance to environmental stresses (Zhao et al 2022). Considering the overall environments, Araripina had the most isolates and higher Shannon's (5.241), Simpson's (0.99) and Margalef 's (7.502) indexes, followed by Nazaré da Mata and Gravatá.…”
Section: Resultsmentioning
confidence: 60%
“…The consequent increase of evapotraspiration further enhances salt accumulation (with the exception of the very dry season where leaf stomata close and traspiration is reduced), exacerbating the process of soil salinization and increasing especially Na + levels in the soil. Moreover, vegetation cover is reduced in halophytic compared to riparian communities, entailing an increase in soil temperature that further boosts salt accumulation due to evaporation (Liu et al, 2019) and causes changes in bacterial community structure (Zhao et al, 2022). Finally, plants can not avoid the passive accumulation of salt in their tissues: this salt is returned to the soil at the end of the growing season, during leaf/root renewal or plant death, supplying salt-enriched litter to the soil and altering OM decomposition.…”
Section: Figurementioning
confidence: 99%